CD4+ T Cell Immune Specificity Changes After Vaccination in Healthy And COVID-19 Convalescent Subjects - Esparcia-Pinedo, Laura; Martínez-Fleta, Pedro; Ropero, Noelia; Vera-Tomé, Paula; Reyburn, Hugh T.; Casasnovas, José M.; Rodríguez Frade, José M.; Valés-Gómez, Mar; Vilches, Carlos; Martín-Gayo, Enrique; Muñoz-Calleja, Cecilia; Sanchez-Madrid, Francisco; et al. (Frontiers in Immunology, 2022)
The immune response promoted by SARS-CoV-2 vaccination is relevant to develop novel vaccines and optimized prevention strategies. We analyzed the adaptive immunity in healthy donors (HD) and convalescent individuals (CD), before and after administering BNT162b2 vaccine. Our results revealed specific changes in CD4+ T cell reactivity profile in vaccinated HD and CD, with an increase in S1 and S2 positive individuals, proportionally higher for S2. On the contrary, NCAP reactivity observed in HD and CD patients was no longer detectable after vaccination. Despite the substantial antibody response in CD, MPro-derived peptides did not elicit CD4+ lymphocyte activation in our assay in either condition. HD presented an increment in anti-S and anti-RBD IgG after first dose vaccination, which increased after the second vaccination. Conversely, anti-S and anti-RBD IgG and IgA titers increased in already positive CD after first dose administration, remaining stable after second dose inoculation. Interestingly, we found a strong significant correlation between S1-induced CD4+ response and anti-S IgA pre-vaccination, which was lost after vaccine administration.